588 Uptake of influenza vaccine in children with diabetes in a UK district general hospital setting – a qualitative survey. (17th August 2022) - Halawa, Eman; Aszkenasy, Mark; Sajjanraj, Kishore
Abstract : Aims: The recommendation of the Joint Committee on Vaccination and Immunization (JCVI), is that all children with diabetes should be offered the influenza vaccine. 1 The objective of this study is to ascertain influenza vaccination(IV) uptake among children and adolescents with diabetes in the district general hospital diabetes clinic population of Stockton-on-Tees and Hartlepool, and the factors associated not having that vaccine. Methods: A cross sectional telephone survey was conducted between May and October 2021 which included children and adolescents with diabetes who had not any influenza vaccination documented on their records for the last 3 years from January 2018 to December 2020. It was a convenient sample of 119 children and adolescents with diabetes. Data was extracted from a register of children and adolescents (18 years or younger) with diabetes at Stockton-on-Tees and Hartlepool area, North East of UK at the outpatient diabetes clinics of North Tees and Hartlepool NHS foundation Trust. After obtaining verbal consent, participants were interviewed using a structured interview of 14 questions. The interviewer ascertained patients' date of diabetes diagnosis, their sources of information about IV, degree of satisfaction with IV information, their perceptions and beliefs about influenza and IV and the effect of the COVID-19 pandemic on their decision. The reasons given for refusal of vaccination were explored. Results: There were 119 children on the diabetes register who had vaccination records on SystmOne ®. Of these, 101(85%) children received the influenza vaccine(IV) at least 1 dose in the past 3 years and 18 (15%) children did not receive any doses of the influenza vaccine in the past 3 years. We successfully interviewed 10 parents or patients by telephone. The overall response rate was 10/18 (55%) as shown in figure 1 . The participants were male in 70% of study population with a median (IQR)age of 16(5.5) years. The majority of participants (80%) did not give a clear reason for refusing IV is significantly common above age of 12 years. One carer mentioned that the child felt unwell after last IV and another carer(10%) was unsure about the benefit of IV. In 30% of our participants, Covid 19 outbreak was the reason for not having IV as carers were afraid that their children will catch Covid 19 if they go for the IV. The other interview findings are shown in table 1 . Conclusion: We concluded that influenza vaccine rejection in children and adolescents with diabetes was without clear reasons in most cases specially in adolescents. Thus, this suggests the importance of recommending a plan identifying a likely convenient point of encounter and minimizing barriers for the patient, is likely to offer better chance of success. In this context, there are plans to improve our local influenza vaccine by offering it at diabetic clinic or in collaboration with the school vaccination. Also, now influenza vaccine could be given to these adolescents coupled with the Covid 19 vaccine after being available to this adolescent age group. Reference: Influenza-The Green Book [ebook] London: PHE. Chapter 19. Influenza. Available at: <https://assets.publishing.service.gov.uk/government/uploads/system/uploads/attachment_data/file/931139/Green_book_chapter_19_influenza_V7_OCT_2020.pdf> [Accessed 11 February 2022].